Effectiveness of Rosemary Aromatherapy Diffuser on Student Learning Outcomes in the Covid 19 Era - Nisa, Rif'atun; Faridasari, Ira (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
In the field of education, Covid 19 has an impact on changes in learning methods and processes, making students often experience boredom, impaired concentration and stress, this can affect student learning outcomes. There are several alternatives that can be done as an effort to improve concentration in learning, one of which is the use of Aromatherapy. Rosemary can eliminate depression, stress, mental tension and lethargy. The purpose of this study was to determine the effectiveness of Aromatherapy Diffuser Rosemary on student learning outcomes in the Covid 19 pandemic era. This research is quantitative with a Quasi Experiment design. Data analysis uses univariate tests to measure variable frequencies. While the bivariate test uses the T-test. Respondents of this study were 100 3rd year students, consisting of students of DIII Midwifery, DIII Nursing and S1 Nursing Study Programs. The dose used was 6 drops of essential oil in a diffuser with 30 ml of water, for 30 minutes each meeting. And carried out for 2 months continuously.Based on the results of the T-test conducted, it can be seen that the significance value is smaller than the alpha value (0.000 <0.05). After the Rosemary Aromatherapy Diffuser intervention was carried out on students routinely in learning activities, respondents experienced an average increase in learning outcomes of 0.204. The results of this study indicate that there is an Effectiveness of Rosemary Aromatherapy Diffuser on Student Learning Outcomes in the Covid 19 Era.